Initial findings of a gap analysis of the digital piracy literature: Six undiscovered countries - Phau, Ian; Lwin, Michael; Goode, S. (Emerald Group Publishing Limited, 2012)
Digital piracy continues to be a problem for firms, industry lobby groups and regulators. The purpose of this paper is to report initial findings of a review of the digital piracy literature. To reduce conceptual overlap and duplicated effort, the author aims to identify gaps in understanding for future research. The paper reviews prior literature on digital piracy across disciplinary areas. Six gaps are identified, being the supply of pirate digital materials, piracy for non-desktop environments, alternative distribution methods, the quality of pirate materials, the behaviour of piracy groups, and the benefits of digital piracy. These gaps constitute important undiscovered areas of knowledge. The paper excludes working papers and practitioner articles, which may contain different insight. The paper reports initial findings only, and the ongoing analysis may shed new light on these findings. The paper contributes by providing a multidisciplinary view of gaps in the literature. No prior study has yet reviewed prior literature with a view to identifying these opportunities for future work. © 2012, Emerald Group Publishing Limited